The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.14336/ad.2023.0311
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Neuroinflammation-Modulating Strategies in Tuberculous Meningitis: Targeting Microglia

Abstract: Tuberculous meningitis (TBM) is the most severe complication of tuberculosis (TB) and is associated with high rates of disability and mortality. Mycobacterium tuberculosis (M. tb), the infectious agent of TB, disseminates from the respiratory epithelium, breaks through the blood-brain barrier, and establishes a primary infection in the meninges. Microglia are the core of the immune network in the central nervous system (CNS) and interact with glial cells and neurons to fight against harmful pathogens and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 253 publications
0
2
0
Order By: Relevance
“…Upon Mtb invasion, the activated microglia release numerous cytokines and chemokines, contributing to the defense against central nervous system infection and neurogenesis-related pathogenesis [13,14]. Activated microglia differentiate into M1 (pro-inflammatory phenotype) and secrete pro-inflammatory cytokines, including IFN-γ, TNF-α/β, and IL-1α/β [15,16], as confirmed in the pneumococcal meningitis animal models [17,18]. However, excessive activation can elicit a nonspecific immune response and damage the nerve tissue [19].…”
Section: Introductionmentioning
confidence: 85%
“…Upon Mtb invasion, the activated microglia release numerous cytokines and chemokines, contributing to the defense against central nervous system infection and neurogenesis-related pathogenesis [13,14]. Activated microglia differentiate into M1 (pro-inflammatory phenotype) and secrete pro-inflammatory cytokines, including IFN-γ, TNF-α/β, and IL-1α/β [15,16], as confirmed in the pneumococcal meningitis animal models [17,18]. However, excessive activation can elicit a nonspecific immune response and damage the nerve tissue [19].…”
Section: Introductionmentioning
confidence: 85%
“…SCI is a CNS disease with high incidence, high disability rate, and very low cure rate, which is mainly caused by falling from high places and car accidents. , SCI mainly includes primary injury caused by mechanical injury and secondary injury caused by various pathological processes. , At present, inhibiting the overexpression of CNS proinflammatory factors caused by secondary injury is considered as one of the main ways to treat SCI. It has been reported that after SCI, overexpression of pro-inflammatory factors and oxidative stress in the injured microenvironment will further aggravate neurotoxicity at the injured site . Therefore, inhibiting the expression of inflammatory factors at the injured site and reducing the degree of oxidative stress have become the focus of this study.…”
Section: Discussionmentioning
confidence: 99%
“…24−26 It has been reported that after SCI, overexpression of pro-inflammatory factors and oxidative stress in the injured microenvironment will further aggravate neurotoxicity at the injured site. 66 Therefore, inhibiting the expression of inflammatory factors at the injured site and reducing the degree of oxidative stress have become the focus of this study.…”
Section: Discussionmentioning
confidence: 99%